Challenges and Opportunities of Reverse Logistics for Biodiversity Conservation in Southern Brazil: An Approach to Environmental Sustainability - Milkievicz, Indianara Ignácio; Borges, Vitor Toledo; Fagundes, Alexandre Borges; Figueiredo, Flavia Borges; Campos, Claudia Guimarães Camargo (Modern Environmental Science and Engineering, 2025)
THIS IS AN ARTICLE PUBLISHED BY Modern Environmental Science and Engineering (e-ISSN: 2333-2581) ON 2025-03-31, AVAILABLE ONLINE: https://doi.org/10.15341/mese(2333-2581)/01-03.11.2025/002 Abstract Reverse logistics is defined as the management of reverse flows of products and materials, from consumption back to their origin. It stands out as a crucial tool for boosting environmental sustainability and mitigating the adverse impacts of human activities on the environment. In southern Brazil, a region rich in natural ecosystem diversity, implementing reverse logistics is highly significant to mitigate the effects of goods production and consumption. However, challenges such as inadequate infrastructure, lack of public awareness, and the need for specific regulations hinder the practice in this region. This study aims to explore options adopted in other countries as models for implementing and utilizing reverse logistics for biodiversity conservation, thereby promoting the dissemination of the circular economy as a critical aspect. Through a literature review, viable solutions and successful examples of reverse logistics applications were sought. Adapting international experiences to the local reality in southern Brazil could contribute to environmental preservation and foster a sustainable, circular economy that is both permanent and resilient. Despite challenges such as infrastructure deficits, public awareness, and regulatory gaps, this study emphasizes the importance of examining successful international models and adapting them to the local context. Government cooperation through laws and decrees is essential to institutionalize reverse logistics practices. By doing so, we can contribute to environmental preservation and promote a sustainable, circular economy in southern Brazil.
Keywords: Reverse logistics; Environmental sustainability; Southern Brazil; Environmental legislation